Management of Congenital Urethral Strictures In Infants. Case Series - Gobbi, Dalia; Fascetti Leon, Francesco; Gnech, Michele; Andreetta, Marina; Midrio, Paola; Gamba, Piergiorgio; Castagnetti, Marco (Urology Journal, 2019)
Purpose: Infra-vesical obstruction is uncommon in infants and generally due to urethral valves. Congenital urethral strictures (CUS), instead, defined as a concentric narrowing of the urethral lumen, are exceedingly rare in infants. Materials and Methods: We reviewed our experience with 7 patients treated at our institution for CUS <age of 1-year. The study is a retrospective review of 7 patients treated for CUS diagnosed <age 1-year during a 10-year period. Result: In a single patient, the urethral stricture was an isolated condition, 3 had a Prune Belly Syndrome (PBS) and the remaining 3 had an Ano-Rectal Malformation (ARM). Four patients had upper tract dilatation detected on prenatal ultrasound. Five patients had upper tract dilatation on postnatal ultrasound. Five patients had impaired renal function at diagnosis and 3 required renal transplantation eventually. On micturating cystourethrography, all strictures were located in the anterior urethra and 4 cases had associated vesicoureteral reflux. In all cases, but one urinating via a patent urachus, initial management included insertion of a supra-pubic catheter. Subsequently, the CUS could be treated by dilatation or endoscopic incision in the 3 patients with Prune belly syndrome, whereas 3 of the remaining 4 required a formal urethroplasty. Conclusion: Diagnosis and treatment of CUS in infants and children remain difficult to standardize. At presentation, urinary diversion is key to avoid progressive renal damage in infants that can already have an impaired renal function. Anterior strictures in patients with PBS are likely to be fixed with progressive dilatation. In other patients, instead, urethroplasty should be considered. A formal vesicostomy or, if possible, an urethrostomy can allow temporizing final surgery. A major problem we experienced in the treatment of CUS is that the small endoscopic instruments required in this age group make urethral instrumentation more difficult and less effective than in older children and adults.